Accelerating solar desalination in brine through ion activated hierarchically porous polyion complex hydrogels. Issue 12 (9th November 2020) - Zhu, Fengbo; Wang, Liqian; Demir, Baris; An, Meng; Wu, Zi Liang; Yin, Jun; Xiao, Rui; Zheng, Qiang; Qian, Jin
Abstract : A hierarchically porous hydrogel (HPH) mediated by a polyion complex enables accelerated solar desalination performance in brine than in pure water. Abstract : Solar-powered water desalination has been considered as one of the most promising solutions to alleviate clean water scarcity. In concentrated brine, the strong hydration ability of ions increases the required energy for water evaporation and thus lowers the desalination performances of most-existing solar vapor generators (SVGs). Here, a novel SVG is reported that exhibits superior desalination performance in brine than in pure water. This SVG is constructed by the complexation of oppositely charged polyelectrolytes into a hierarchically porous hydrogel (HPH), with interpenetrated polyaniline as efficient light absorbers. With controlled thermal management, the evaporation rate of this HPH-based SVG is 2.79 kg m −2 h −1 in simulated brine (3.5 wt% NaCl solutions) under one sun illumination, 67% higher than that in pure water (1.67 kg m −2 h −1 ) and more prominent than existing salt-resistant SVGs. Desalination tests with real seawater indicate that HPH is salt-resistant and sustainable for fast freshwater production. All-atom molecular dynamics simulations indicate that the unique interactions between the oppositely charged groups of the polyion complex and the mobile ions in brine can alter the water state, resulting in enhanced hydrability of the polymeric skeleton. This work provides a new approach for the development of next-generation SVGs with enhanced solar desalination performance.